Exchange-Traded Commodities as New Financial Instruments on the Warsaw Stock Exchange – Regulatory Challenges from a Comparative Perspective - Opoka, Marcin (Journal of Finance and Financial Law, 2024)
The purpose of the article. This article examines Exchange-Traded Commodities (ETCs), prompted by the introduction of the first ETC on the Warsaw Stock Exchange (GPW) in August 2023, a significant milestone in the evolution of Poland's capital market. The analysis focuses on the regulations introduced by the GPW in Warsaw, evaluating the adequacy of measures aimed at protecting ETC purchasers. The study also incorporates a European perspective, offering a comparative analysis of national solutions. The structure of the instrument, regulatory framework, origins, and principles of ETC operation are examined, distinguishing these instruments from more popular ETFs. Despite some similarities, ETCs differ significantly in structure and legal character from ETFs, particularly due to the lack of harmonisation at the European level, which impacts investor protection. This disparity raises questions about the effectiveness of existing regulations in ensuring investor safety and trading certainty, not only in Poland. Methodology. To answer these questions the research utilizes a mixed-method approach, incorporating literature reviews, legal acts analyses, and market data examination. It employs a comparative analysis to explore the functionalities, structures, and regulatory settings of ETCs versus ETFs, with a particular focus on mechanisms for investor protection. Additionally, the study evaluates and contrasts the trading regulations applicable to ETCs across major European exchanges in relation to the regulatory frameworks and investor protections implemented by the Warsaw Stock Exchange. Results of the research. The analysis concludes that the lack of harmonised regulations for ETCs poses a significant challenge for investors. In practice, investors are often protected in key aspects at a level similar to that of ETF investors. However, these are not universal or guaranteed regulatory standards that investors can rely on. Therefore, it is recommended to standardise the terminology of passive investment instruments (including ETCs), leading to the harmonisation of basic principles for the construction and trading of these instruments. Regarding ETCs on the Warsaw Stock Exchange, the introduced solutions provide a higher level of investor protection compared to some other EU markets. Nonetheless, further regulatory changes are proposed to support the continued development of the ETC market in Poland.